First results of the differential cross sections of 9Be(d,d0) at energies and angles suitable for Elastic Backscattering Spectroscopy - Ntemou, E.; Kokkoris, M.; Lagoyannis, A.; Lungu, C.; Mergia, K.; Preketes-Sigalas, K.; Tsavalas, P. (HNPS Advances in Nuclear Physics, 2019)
The differential cross sections of the 9Be(d,d0) elastic scattering were determined in the present work in the energy range of Ed,lab = 740 - 2200 keV in variable steps, mainly 20 keV at five backscattering angles (120o, 140o, 150o, 160o and 170o). The measurements were performed at the 5.5 MV TN11 HV Tandem Accelerator of the N.C.S.R. “Demokritos” implementing a high precision goniometer. The target used was a thin Si3N4 target with a Beryllium layer on top. The obtained differential cross section values are compared to the ones existing in literature and the observed similarities and discrepancies are discussed.